THE ROLE OF URIFFM IN THE DEVELOPMENT OF UKRAINIAN FOREST SCIENCE - Tkach, V. P.; Meshkova, V. L. (Forestry and Forest Melioration, 2018)
A brief history of Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM) is presented. Characteristics of stationary researches of the Institute and its network of experimental stations are given. Achievements and perspective research on some problems are described. Importance of geographical approach and accounting forest site conditions during forest research is accented. Further investigations of URIFFM must be also directed on the ground of the ways of improvement the environmental role of forests of Ukraine in conditions of global environment change, increase the biological stability of forests, the mitigation due to the forests the consequences of climate change, on forest protection from fire, pests and diseases, and on solution of important national problems connected with the urgent need to increase the forest growth potential and forest coverage in Ukraine to optimal level. Standards and recommendations of URIFFM were and remain the basis of development of forest science in Ukraine, and transition of the forest management to the ways of sustainable development.